Let's Talk: African Caribbean Women, Mothering Motherhood, and Well-Being - Brown, Geraldine (Frontiers in Sociology, 2020)
In the UK, African Caribbean women's experiences of mothering and motherhood are often studied in isolation from how “race” structures and shapes their lives and everyday health and well-being. This failure to connect women's wellbeing and racialized injustices also occurs in debates around “gangs” and “urban gun crime” (UGC). The women's experiences and the effects on their health and well-being are absented from the discussions. This paper, based on my doctoral research, uses an intersectional analysis to explore the views of mothers engaged in community activities to limit “urban gun crime.” Like me, they defined themselves as of Black Caribbean heritage and we created “spaces” where we could “reason,” share experiences of womanhood, motherhood and mothering in a racist society and centre what is habitually ignored. They highlight the importance of getting mothering “right” with the stress and anxiety about the dire consequences of getting it “wrong.” They show their love, commitment and aspirations for their child/ren and the emotional and intellectual labor needed in their daily strategies to keep them from harm caused by state institutions and life “on road.” The research confirms the impact of “race,” racialization and racism to our lives and experiences of health and well-being and raises critical questions for the dominant and normative views of mothering and/ or motherhood that underpin UK policy and practice.